The cognitive rehabilitation of a sample of children living with HIV : a specific focus on the cognitive rehabilitation of sustained attention - Basterfield, Candice (Rhodes University, Faculty of Humanities, Department of Psychology, 2015)
Pharmacological interventions to treat Human Immunodeficiency Virus (HIV) with antiretrovirals (ARVs), have dramatically improved the survival rates of HIV positive children maturing into adulthood. However, HIV-associated neurocognitive decline still persists in the era of ARVs. Within the framework of brain plasticity, a number of researchers have begun to assess the feasibility of cognitive rehabilitation therapy as a complement to ARVs to reverse neurocognitive decline as a result of HIV (e.g., Becker et al., 2012). Only one study has been conducted in South Africa, by Zondo & Mulder (2014), assessing the efficacy of cognitive rehabilitation in a paediatric sample. The current research builds on the above mentioned study by implementing an experimental approach to examine the effect of cognitive rehabilitation in a sample of both HIV positive and HIV negative children. Five HIV positive and six HIV negative children were assigned to either an experimental or control group. The experimental group underwent two months of cognitive rehabilitation therapy remediating sustained attention, whereas the control group took part in placebo activities. Sustained attention measures were taken before and after the intervention training sessions, using a sustained attention subtest from the Test of Everyday Attention for Children (TEA-CH). A Mann Whitney U Test revealed that the experimental group (Mdn=38.50) did not differ significantly from the control group (Mdn = 37.00) after the cognitive rehabilitation intervention, U=12.00, z= -.55, p= .66, r= -.17. But a Wilcoxon Signed Rank Test found that there was a significant improvement from pretest scores (Mdn=31.00) to posttest scores (Mdn=38.00) following the rehabilitation for HIV positive participants in the sample, T=15.00, z = -2.02, p= .04, r= -.90. This raises the possibility that cognitive rehabilitation could be used as a low cost intervention in underdeveloped contexts
Keywords: HIV-positive children -- Rehabilitation; Antiretroviral agents; HIV (Viruses) -- Side effects; Brain damage -- Patients -- Rehabilitation; Cognition disorders -- Patients -- Rehabilitation